Sistem Pakar Mendiagnosa Kerusakan Laptop untuk Membantu Menemukan Masalah Berbasis Web Menggunakan Metode Forward Chaining - Dahri, Syamsul; Basri, Hasan; Annafiyah, Ika Komala; Yulistio, Tabah; Saifudin, Aries; Kusyadi, Irpan (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Artificial intelligence is computer science that studies how to activate machines (computers) to complete work done by humans, even better than work done by humans. A broken laptop is a common problem, and expert systems are designed to help technicians solve the problem. Therefore, by using the network-based forward link method, an expert system application program was created to identify damaged laptops. The forward link method is a search method based on data or facts, then the collected facts are matched with the IF part of the IF-THEN rule. The expert system can identify damage based on signs of damage determined by the rules and implemented through the forward link method in the process of determining signs of damage. This application is here to make it easier for users to detect damage that occurs so they can solve problems more quickly and accurately.